Clinical and Cost-effectiveness of a Pre-exposure Prophylaxis (PrEP) Programme to prevent HIV - O Murchu, Eamon (Trinity College Dublin. School of Medicine. Discipline of Public Health & Primary Care, 2021)
Introduction There has been an increase in HIV notifications in recent years in Ireland. PrEP is a form of HIV prevention whereby oral antiretrovirals are taken by HIV-negative individuals to prevent infection. The aim of this study is to assess the clinical and cost-effectiveness of providing a publicly funded PrEP programme in Ireland. Methods A Health Technology Assessment was undertaken, following both national (HIQA) and international (EUnetHTA and ISPOR) methodological and reporting guidelines. A systematic review and meta-analysis of randomised controlled trials (RCTs) was undertaken to assess the clinical effectiveness and safety of PrEP. A full economic evaluation was undertaken to assess the cost-effectiveness and budget impact of introducing a national PrEP programme. The economic evaluation included an original state transition Markov model populated with Irish cost and epidemiological parameter data. Results Clinical effectiveness The systematic review retrieved fifteen RCTs that met our inclusion criteria. Included studies involved 25,051 participants encompassing 38,289 person-years of follow-up data. Populations included Men who have Sex with Men (MSM), serodiscordant couples (where one person is HIV positive and the other HIV negative), People Who Inject Drugs (PWID) and heterosexuals at high risk. Risk of bias was judged to be low in all studies. PrEP was found to be effective in MSM (relative risk [RR] 0.25, 95% CI: 0.1 to 0.61, 5,103 person-years of data, high certainty), serodiscordant couples (RR 0.25, 95% CI: 0.14 to 0.46, 5,237 person-years of data, high certainty) and PWID (RR 0.51, 95% CI: 0.29 to 0.92, 9,666 person-years of data, high certainty), but not in heterosexuals (non-significant). With high adherence (>80%), risk in MSM was reduced to 0.14 (95% CI: 0.06 to 0.35). Efficacy was strongly associated with adherence (p<0.01); on average, a 10% increase in adherence increased efficacy by 13%. PrEP was found to be safe, however unrecognised acute HIV at enrolment increased the risk of viral drug mutation (RR 3.53, 95% CI: 1.18 to 10.56). Evidence for risk compensation was not found. Cost-effectiveness In the base case, PrEP was found to be more effective and less costly than not providing PrEP (cost saving). Univariate deterministic sensitivity analysis demonstrated that the efficacy of PrEP and the incidence of HIV in high-risk individuals had the greatest impact on the cost-effectiveness. The inclusion of an increase in STIs due to risk compensation had a negligible impact on the results. Two-way sensitivity analysis demonstrated that incremental cost-effectivenss ratios (ICERs) were negatively associated with both the uptake rate and the size of the eligible population (proportion of MSM who are at high risk). Efficacy was a significant driver in the model. PrEP was cost saving at all efficacy values above 60%, and at an efficacy of 44% (the lowest recorded efficacy in MSM [iPrEX trial]), the ICER was 4,711/QALY (highly cost-effective). A scenario analysis was performed where the PrEP regimen followed event-based dosing (administration during high risk periods only). As expected, event-based dosing was associated with a lower ICERs. Budget impact The incremental budget impact was estimated at almost 1.5m in the first year (95% CI: 0.5m to 3m) and 5.4m over five years (95% CI: 1.8m to 11.5m). Also modelled was the number of HIV infections estimated to occur with and without a PrEP programme in place. Overall, 173 HIV infections were estimated to be averted over the course of five years. Extending beyond five years, the yearly incremental budget impact becomes negative (cost saving) by Year 8 (- 0.2m; 95% CI: - 2m to 1.7m). In terms of the aggregate budget impact, the break even point is reached in Year 14 (all programme and medication costs will have been recovered). Conclusions High certainty evidence exists that PrEP is safe and effective in MSM, serodiscordant couples and PWID. Additional research may be needed prior to recommending PrEP in heterosexual individuals. PrEP was found to be cost saving in the first cost-effectiveness analysis of a population-based PrEP programme in Ireland. Including a potential increase in STIs (other than HIV) due to risk compensation had a negligible impact on the results. The adoption of event-based dosing could lead to additional cost savings. The incremental budget impact is modest, with evidence of cost savings in as little as eight years.
APPROVED